Depth interactions and reproductive ecology of sympatric Sillaginidae: Sillago robustaand S. flindersi - Gray, C.; Barnes, L.; Van der Meulen, D.; Kendall, B.; Ochwada-Doyle, F.; Robbins, William (Inter-Research Science Center, 2014)
This study examined whether differences existed in the depth distributions and reproductive strategies of the co-occurring Sillago robusta and S. flindersi in coastal waters off eastern Australia. Marked spatial and temporal dis similarities in demography and reproduction were observed between the 2 species, with S. robusta being more abundant in the shallow (15-30 m) strata and S. flindersi in the mid (31-60 m) strata, with neither species being consistently abundant in the deep (61-90 m) strata. The size composition of S. robusta was similar across depths, but smaller and immature S. flindersi predominantly occurred in the shallow strata, with larger and mature individuals occurring deeper. These data indicate partitioning of habitat resources, which may aid species coexistence. Both species potentially spawned year-round, which is probably an adaptation to the region's dynamic coastal environment. However, a greater proportion of S. robustawas in spawning condition between September and March, whereas S. flindersi displayed no such temporal pattern. Maturity ogives differed significantly between sexes and locations for both species. Both species displayed similar ovarian development, with females having multiple concurrent oocyte stages, indicating potential multiple spawning events as evidenced in other Sillaginidae. For both species, estimated batch fecundity increased with fish length, but S. robustahad a greater fecundity at any given length than S. flindersi. In contrast, S. flindersi potentially produced larger-sized eggs and invested greater energy into gonad development than S. robusta, indicating the 2 species have evolved slightly different reproductive strategies. Despite this, both species are subjected to substantial trawl fisheries, which may have already impacted their reproductive ecologies. © The authors 2014.